Targeted Alpha Therapy in mCRPC (Metastatic Castration-Resistant Prostate Cancer) Patients: Predictive Dosimetry and Toxicity Modeling of 225Ac-PSMA (Prostate-Specific Membrane Antigen) - Belli, Maria Luisa; Sarnelli, Anna; Mezzenga, Emilio; Cesarini, Francesco; Caroli, Paola; Di Iorio, Valentina; Strigari, Lidia; Cremonesi, Marta; Romeo, Antonino; Nicolini, Silvia; Matteucci, Federica; Severi, Stefano; et al. (Frontiers in Oncology, 2020)
Radioligand therapy is a type of internal radiotherapy combining a short-range radioisotope labelled to a carrier with high affinity for a specific receptor expressed on tumor cells. Targeted alpha therapy (TAT) combines a high-LET emitter (225Ac) with a prostate-specific membrane antigen (PSMA) carrier specifically binding tumor cells in patients with metastatic castration-resistant prostate cancer (mCRPC). Whilst the antitumor activity of 225Ac-PSMA is well documented, this treatment is nowadays only used as salvage therapy because the therapeutic window is limited by the high incidence of xerostomia. Thus methods to reduce salivary toxicity and models able to describe xerostomia incidence are needed. We recently studied the efficacy of salivary gland protectors administered in combination with 177Lu-PSMA therapy. Starting from these data, we performed a predictive dosimetric evaluation of 225Ac-PSMA to assess the impact of salivary gland protectors in TAT. 225Ac-PSMA predictive dosimetry was performed in 13 patients treated with 177Lu-PSMA. Sequential whole-body planar images were acquired 0.5-1 h, 16-24 h, 36-48 h and120 h post-injection. 177Lu time-activity curves were corrected for 225Ac physical decay and assumed in equilibrium for all daughters. The OLINDA/EXM spherical model was used for dose estimation of parotid and submandibular glands (PGs, SGs). Dose for each daughter was calculated and summed for the total dose estimation. The biologically effective dose formalism was extended to high-LET emitters (BEDH). For the total BEDH, including the contribution of all daughter isotopes, the brachytherapy formalism for a mixture of radionuclides was implemented. Equivalent doses in 2Gy/fraction (EQD2) were then calculated and compared with Normal Tissue Complication Probability (NTCP) model derived from External Beam Radiotherapy (EBRT) for grade≥2 xerostomia induction. Median predictive doses were 0.86 BdRBE5/MBq for PGs and 1.05 BdRBE5/MBq for SGs with 53% reduction compared to previously published data. The results show that the radiobiological model implemented is conservative as it overestimates the complication rate with respect the clinical data. Our data shows the possibility of reducing salivary gland uptake in TAT with the co-administration of organ protectors but these results should be confirmed for TAT with 225Ac-PSMA by carrying out prospective trials with defined toxicity endpoints and dosimetry procedures.